Немецкий язык для сотрудников высшей школы (нелингвистического профиля): учебное пособие - Прохорец Е. К. Елена Константиновна; Овчинникова О. М. Ольга Михайловна; Беленюк Т. Н. Тамара Николаевна; Александров О. А. Олег Анатольевич (Томск, Изд-во ТПУ, 2014)
Заглавие с титульного экрана